Contributions of Islamic Banks to the Palestinian Banking Activity - Ghassan Da'as; Tareq Al-Haj (My University, 2003)
The main purpose of this research is to investigate the contributions of Islamic banks to the Palestinian banking activity, by investigating the policies of commercial and Islamic banks according to assets, deposits, financial facilities, and external financial use of banking funds. To do so, The data were analyzed using the statistical parameter Wilks, lambda. The results indicate that there are no significant differences between commercial and Islamic banks according to credit policy concerning assets, deposits, financial facilities, and external financial use of banking funds. Some result points were proposed in order to assist in raising the Islamic banks portion at Palestinian banking activity.